2012
DOI: 10.5012/bkcs.2012.33.3.917
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences of Glycerol in the Gas Phase and in Water

Abstract: The conformational study of glycerol has been carried out using the M06-2X/cc-pVTZ level of theory in the gas phase and the SMD M06-2X/cc-pVTZ level of theory in water in order to understand its conformational preferences and solvation effects. Most of the preferred conformers of glycerol have two C5 hydrogen bonds in the gas phase, as found by the analysis of calorimetric data. It has been known that the solvation drove the hydrogen bonds of glycerol to be weaker and its potential surface to be fatter and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Glycerol has three flexible hydroxyl groups, and the formation of intramolecular hydrogen bonds contributes to a substantial increase in the number of isomers (e.g., 126 isomers have been reported) . Thus, over the years, several theoretical and experimental ,,,, studies have investigated glycerol conformations. In this work, we selected 10 glycerol configurations from literature and 10 from MD simulations following the same procedure outlined in section in Theoretical Approach and Computational Details Section.…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol has three flexible hydroxyl groups, and the formation of intramolecular hydrogen bonds contributes to a substantial increase in the number of isomers (e.g., 126 isomers have been reported) . Thus, over the years, several theoretical and experimental ,,,, studies have investigated glycerol conformations. In this work, we selected 10 glycerol configurations from literature and 10 from MD simulations following the same procedure outlined in section in Theoretical Approach and Computational Details Section.…”
Section: Resultsmentioning
confidence: 99%
“…Bastiensen [ 137 ] studied the structure by electron diffraction, and found the αα and αγ conformers as the major species. The symbols α, β, and γ refer to the heavy atom torsional positions, irrespective of the hydroxy-hydrogens positions (see [ 137 , 147 ]). He concluded that there are two intramolecular H-bonds for glycerol, which have three hydrogen-bond donor (and acceptor) OH groups.…”
Section: Conformational Equilibriamentioning
confidence: 99%
“…He concluded that there are two intramolecular H-bonds for glycerol, which have three hydrogen-bond donor (and acceptor) OH groups. Gas-phase studies by Jeong et al , [ 147 ] at the M06-2X level and by Callam et al , [ 148 ] at the G2(MP2) and CBS-QB3 levels deviate slightly regarding the conformer composition at T = 298 K. The most populated conformer is the αγ structure followed by αα or γγ. The free energies differ by less than 1.4 kJ/mol for the two most stable species by the different methods, thus the results are fairly method and basis set dependent.…”
Section: Conformational Equilibriamentioning
confidence: 99%
“…In an implicit solvation setting, Jeong et al 42 obtained the conformational preference of glycerol at the M06-2Z/cc-pvtz level of theory in the aqueous phase. It is shown that glycerol exists as an ensemble of many feasible configurations due to weakened intramolecular hydrogen bonding.…”
Section: ■ Introductionmentioning
confidence: 99%